LOCATING STATE ACTORS IN VIOLENCE AGAINST CHILDREN (VAC) NETWORKS IN KENYA: A COMPLEXITY LEADERSHIP LENS - Nassimbwa, Jacqueline; Kakuru, Doris M.; Mpamizo, Malcolm T. (International Journal of Child, Youth and Family Studies, 2022)
Kenya has made significant efforts to address violence against children (VAC), but its prevalence remains high. Networking of different actors has shown evidence of benefit in some sectors, but determining its effectiveness in addressing VAC has not received due scholarly attention. We conducted qualitative research, including a desk review, focus group discussions, and interviews. In this article, we apply complexity leadership theory to illuminate the types of networks involved and the influence Kenya’s government actors can exert towards eliminating VAC. We found that these actors operate through structured and unstructured networks. The latter are mainly grassroots responders who work voluntarily. The complexity leadership theory postulates that leadership influence is exercised through key functions, which are reflected in the two types of networks. The political–administrative function in Kenya is shaped by law; we show how it transforms other networks via an adaptive function. An enabling function is executed through enforcing policy, monitoring, and other methods, while a dissemination function involves the translation of ideas into policy, such as the transformation of Childline Kenya, a grassroots organization, into the National Child Helpline. We conclude that government should strengthen child rights networking by building more technical and financial capacity for this role.